l-Rajz in the Diwan of Ibn Nubatah Al-Masry (d: 768) (Damascus University Journal of arts and humanities sciences, 2025)
Ibn Nubtah Al-Misri is considered one of the most important writers of the eighth century AH; as he left us a rich literary legacy - in poetry and prose - in several works that enrich the taste of the recipient, and open horizons for researchers to delve into studying his literature and contemplating it with true contemplation. Between the pages of this research, the Rajz in his collection was studied in order to reveal the extent of the poet's ability to move it from the fields of verbal strangeness and linguistic complexity to the levels of ease and clarity of meaning, and thus transcend the familiar and prevailing. This research deals with the concept of Rajz and the stages of its developmentthroughout the ages, up to the Mamluk era. It then presented a descriptive study of the Rajz themes in Ibn Nubatah’s collection of poems, including its pieces and arajiz. It then concluded with a statistical prosodic study that demonstrated the poet’s literary ability to absorb the versatility and flexibility of the Rajz meter, and his exploitation of these capabilities in employing his psychological and social state.
Keywords: Rajz; Orjouza; Mamluk Era; Ibn Nubatah Al-Misri